RURAL ECONOMY IN THE PRODUCTION OF PRODUCTS AND ITS PLACE IN THE NATIONAL ECONOMY - Tukhtaboev , Mokhirjon Rakhimzanovich (Educational Research in Universal Sciences, 2023)
The article presents the main scientific developments of the national economy in recent years: filtering and sorption nonwoven fabrics; Biologically active nonwoven materials, providing comfortable conditions for human life; - nonwoven materials filled with Nano scale components.